Uji Vigor Kekuatan Tumbuh Benih Padi (Oryza sativa L.) pada Kondisi Kekeringan dengan Pengaplikasian Pupuk Organik Cair - Rizka Rahmahwati; Ibrahim; Hatuala, Mujuna (Jurnal Sains dan Pendidikan Biologi, 2025)
High seed vigor is one of the determining factors for the successful early growth of rice (Oryza sativa L.). However, drought stress often becomes a constraint in rice cultivation because it can inhibit water imbibition, reduce germination, growth synchrony and decrease the vigor index. Therefore, efforts are needed to maintain seed vigor in water limited conditions, one of which is through the application of liquid organic fertilizer (LOF) from goat manure. This study aims to examine the effect of the application of liquid organic fertilizer from goat manure on rice seed vigor under drought conditions. The parameters observed were germination power, growth synchrony and vigor index. The results showed that the application of 50 mL and 100 mL of goat manure LOF had a significant effect on germination power, growth synchrony and vigor index. This is because the organic acid content from the fermentation of LOF is able to dissolve and wash out some of the dissolved salts. Goat manure organic fertilizer (LOF) contains macronutrients (N, P, K), micronutrients and fermented organic compounds that support seed metabolism, stimulate root growth and improve plant adaptation to drought conditions. Keywords: Seed Vigor, Drought, Rice (Oryza sativa L.), Goat Manure Liquid Organic Fertilizer